Faktor-Faktor yang Memengaruhi Praktik Swamedikasi pada Ibu Hamil di Jawa Tengah - Aisyah, Diah; Sitorus, Jeffry Raja Hamonangan (Seminar Nasional Official Statistics, 2023)
Self-medication is a treatment often chosen by the community to overcome their health complaints. Self-medication must pay attention to special conditions such as pregnant women because the risk of using drugs can impact the health of the mother and fetus. Morever, information about the effects and safety of drugs for pregnant women is still limited. Central Java has the highest percentage of self-medication in 2021, reaching 82.79 percent. Therefore, this study aims to determine the factors at the individual and regional levels that significantly influence the practice of self-medication among pregnant women in Central Java. This study used multilevel binary logistic regression method with data from Susenas Kor's March 2021, publications from BPS and Central Java Health Office. The results showed that age and severity of health problem are individual factors, in addition to GRDP per capita is regional factor that significantly influence the practice of self-medication in pregnant women.